Traduzindo saberes em emergência: por uma epistemologia anarquista da educação museal brasileira - Consiglio, Thiago (Universidade Federal de São Carlos, 2025)
This research take as its central theme the concept of Museum Education and its epistemology. Considering the current state of the field in a phase of consolidation, there are theoretical challenges to be faced on the path toward its emergency, such as the precarious conditions of the area or of the lack of recognition among peers. For this the study utilizes translation as its methodology which enables the articulation of different points of view, inspired by an anarchism, both political and epistemological. The thesis is presented through the narrative of a simbolic journey that initiates in the desert of difficulties, translating the current limitations of the field; after this, in order to heal and rehydrate, it seeks out the fountains, historical fountains to estabilish a relationship of appropriation, translating autonomy and creation; continuing, the path goes into the forest to describe the educational process of discovery, translating language into educational action; further ahead, it presents the Navigation Map, as a structuring metaphor of the work organizing epistemological elaboration, translating an orientation tool into an instrument of action; from this theoretical-methodological basis, a process of cartography is initiated to imagine the possibilities of the emergence of this concept, composed of a territory and a settlement, a space of political articulation among dispersed perspectives with the goal of collective recognition; in the end, the path takes a detour into the woods to explore an insurgent subjectivity which caracterizes the proposal of Museum Education as it is experimented within this work.
Translating emergent knowledges: toward an anarchist epistemology of museum education in brazil
Keywords: Educação Museal; Epistemologia; Tradução; Linguagem; Anarquismo; Museum Education; Epistemology; Translation; Language; Anarchism; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades